Posisi Fatwa dalam Diskursus Pemikiran Hukum Islam - Sofyan A. P. Kau (Al-Ulum, 2010)
Fatwa is a dynamic product of Islamic law. As a result of ijtihad, the presence of a fatwa does not stand alone. Hermeneutically, there are many factors that influence the inference-making legal decisions (fatwa), although theoretically the legal decision based on legal texts and particular methodology. This paper shows that there have been methodological inconsistencies in the fatwa. Fatwa is typically based on conventional methods, i.e., by referring to the al-Quran, Hadith, Consensus and kiyas. However, in certain cases, this method is not applied. This is due to several factors including ideological factor.